Nuclear CK19-immunopositive pseudoinclusions as a new additional objective diagnostic feature of papillary thyroid carcinoma - Domagala, Pawel; Domagala, Wenancjusz (Polish Journal of Pathology, 2020)
One of the key parameters in the diagnosis of papillary thyroid carcinoma (PTC) are true nuclear pseudoinclusions (NPs), which constitute invaginations of the cytoplasm into the nucleus. On the other hand, strong cytoplasmic expression of CK19 is a well-known attribute of PTC tumor cells. We analyzed NPs using CK19 immunohistochemistry in histological sections of 52 PTCs and seven noninvasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTPs). Strong CK19+ NPs were present in 77% of PTCs, whereas NPs in hematoxylin and eosin (HE)-stained slides (HE NPs) were identified in only 48% of PTCs. Detection of CK19+ NPs enabled easier and objective recognition of NPs and better discrimination of NPs from pseudo-pseudoinclusions than detection of HE NPs. In the 15 of the 27 (55.5%) PTCs in which we could not discern HE NPs, strong CK19+ NPs could be identified reliably, quickly and easily. Moreover, all NIFTPs were negative for both CK19+ NPs and HE NPs. Detection of CK19+ NPs may refine the assessment of this important diagnostic feature and, hence, the microscopic diagnostic criteria of PTC. Thus, these findings may have implications for the accurate diagnosis of PTC and NIFTP.